Advances in culture and psychology volume 1 - Chiu, Chi-yue 1963-; Gelfand, Michele J.; Hong, Ying-yi 1964- (Oxford Oxford University Press, 2011)
With applications throughout the social sciences, culture and psychology is a rapidly growing field that has experienced a boom in publication over the last decade. Comprising chapters from internationally renowned culture scholars, this book represents diversity in the theory and study of culture within psychology.
Human culture in evolutionary perspective -- Culture, emotion, and expression -- Infectious disease and the creation of culture -- Attachment, learning, and coping -- Culturally situated linguistic ecologies and language use -- Micro-macro dynamics of the cultural construction of reality -- Horizontal and vertical individualism and collectivism.
Includes bibliographical references and index
Keywords: Culture; Ethnopsychology